Particle Swarm Optimization Untuk Sistem Informasi Penjadwalan Resource Di Perguruan Tinggi - Mansur, Mansur; Prahasto, Toni; Farikhin, Farikhin (Universitas Diponegoro, 2014)
Course timetabling management information system is a system focusing on data management resource and constraints in optimizing the use of available resources and avoid clashing in the process of making class timetabling, so that the resulting information will be effective. Results of such information may assist the college in planning the use of space, and to develop programs of study. Data resource and constraints are implemented using timetabling information system with PSO algorithm. The results of the data analysis using the PSO algorithm by combining six hard constraint and two soft constraints cannot produce an optimal solution, because there are still clashing lecturer-timeslot (soft1), but without combining both soft constraints can produce maximum solutions in the use of the room, where the solution with the best fitness value (0.333), c1(2,0), c2(2,0), w(0,2), and maximum of 10 iterations of the desired solution. The final results are timetabling management information system for resource utilization that generates class timetable information and use of the room. Â Keywords : Management information system; PSO algorithm; Resource; Constraints; Course timetabling; Higher education